Motivation of farmers in crystal guava seed business in bonorowo district, kebumen regency - Ahmad Faisal Anzahri; Yunanto; Zuhud Rozaki (Fakultas Pertanian Universitas Majalengka, 2023)
This study aims to determine the motivation of farmers in crystal guava farming and factors related to farmers' motivation in crystal guava farming in Bonorowo District, Kebumen Regency. The number of respondents in this study was 38 crystal guava farmers. The analysis used is descriptive analysis, scoring techniques, and Spearman Rank correlation analysis. The results show that the motivation of farmers in crystal guava farming is seen from the need for existence, the need for relatedness, and the need for growth is in the high category. Overall, motivation is also classified as high with a score of 50.7. Internal factors that have a significant relationship with existence are land area, amount of production, and income, but no significant relationship was found from internal factors with farmer relatedness, while with growth, namely land area, amount of production, and income. And internal factors that have a significant relationship with the level of farmer motivation include land area, amount of production, and income. External factors that have a significant relationship with existence are the availability of capital assistance and local cultural suitability, but no significant relationship from external factors with relatedness and growth was found. The external factors that have a significant relationship with the level of farmer motivation include capital assistance and local cultural suitability. There needs to be support from across stakeholders so that farmers' motivation can be increased.